Adverse events associated with hepatic arterial infusion chemotherapy and its combination therapies in hepatocellular carcinoma: a systematic review - Wu, Ying; Zeng, Zhenpeng; Chen, Shuanggang; Zhou, Danyang; Tong, Gangling; Du, Duanming (Frontiers in Immunology, 2025)
BackgroundHepatic arterial infusion chemotherapy (HAIC) has emerged as a promising treatment for unresectable hepatocellular carcinoma (HCC). However, the safety profiles of HAIC and its various combination therapies remain to be systematically evaluated.MethodsWe systematically searched PubMed, Embase, Cochrane Library, and Web of Science databases from inception to November 2024. Studies reporting adverse events (AEs) of HAIC monotherapy or combination therapies in HCC were included. The severity and frequency of AEs were analyzed according to different treatment protocols.ResultsA total of 58 studies (11 prospective, 47 retrospective) were included. HAIC monotherapy demonstrated relatively mild toxicity, primarily affecting hepatobiliary (transaminase elevation 53.2%, hypoalbuminemia 57.2%) and hematological systems (anemia 43.0%, thrombocytopenia 35.2%). HAIC with targeted therapy showed increased adverse events, including characteristic reactions like hand-foot syndrome (48.0%) and hypertension (49.9%). HAIC combined with targeted, and immunotherapy exhibited the highest adverse reaction rates (neutropenia 82.9%, transaminase elevation 97.1%), while HAIC with anti-angiogenic and immunotherapy showed a relatively favorable safety profile. Prospective studies consistently reported higher incidence rates than retrospective studies, suggesting potential underreporting in clinical practice.ConclusionsDifferent HAIC-based regimens exhibit distinct safety profiles requiring individualized management approaches. We propose a comprehensive framework for patient selection, monitoring strategies, and AE management. These recommendations aim to optimize treatment outcomes while minimizing adverse impacts on patient quality of life.